Comparative Evaluation of Shear Bond Strength: 3D-Printed Composite Versus Zirconia and E-max on Feldspathic Ceramic Rods Using Two Resin Cements - Fahmi, Mohammed K. (European Journal of Dentistry, 2025)
This article aims to evaluate the shear bond strength of a 3D-printed composite resin compared with well-established materials (zirconia and E-max), bonded with two different resin cements: Panavia V5 and ResiCem EX.Shear bond strength was tested across six material–cement combinations: zirconia, E-max, and 3D-printed composite resin, each bonded with either Panavia V5 or ResiCem EX. A total of 24 discs were prepared from each material, with 12 specimens allocated to each group (10 tested bond strength and 2 microscopy). The bonding interfaces were examined using a digital optical microscope. Shear bond strength was measured using an Instron universal testing machine, and statistical analysis was performed using one-way and two-way ANOVA.The highest shear bond strength was observed in 3D-printed composite resin bonded with Panavia V5 (20.74 MPa), which was significantly higher than zirconia bonded with ResiCem EX (13.9 MPa, p = 0.010). No significant differences were noted between the remaining material–cement combinations.3D-printed composite resin demonstrated superior bond strength compared with zirconia and E-max; Panavia V5 showed potential as a reliable cement for clinical applications. These findings support the growing role of 3D-printed composites in restorative dentistry.
Keywords: zirconia; E-max; 3D-printed composites; shear bond strength; Panavia V5; ResiCem EX; dental restorations